The Implementation of Child-Friendly School Policy from the Perspective of Islamic Educational Management (A Case Study at Trenggalek) - Ustadiatu Munawaroh, Luluk; Masrokan Mutohar, Prim (Studia Manageria, 2025)
This study aims to analyze the implementation of the Child-Friendly School (CFS) policy from the perspective of Islamic education management at State Senior High School 2 Trenggalek. The research focuses on four main aspects: planning, implementation, supervision, and evaluation of the policy. A qualitative approach with a case study design was employed, in which data were collected through in-depth interviews, observations, and documentation, and then analyzed using Miles, Huberman, and Saldaña’s interactive model. The findings reveal that policy planning was carried out participatively through deliberation involving the principal, teachers, students, and the school committee. Policy implementation was reflected in participatory teaching methods, the creation of a more conducive school environment, and the provision of counseling services, although constrained by limited resources and teacher training. Policy supervision was conducted through formal mechanisms such as complaint boxes and counseling services, alongside informal forums involving students, reflecting a participatory monitoring pattern. Policy evaluation was conducted periodically and showed an increase in students’ awareness of anti-violence values, despite challenges such as teacher resistance to change and budget constraints. The study concludes that the implementation of the CFS policy at State Senior High School 2 Trenggalek can be harmonized with the principles of Islamic education management al-takhthith, al-tanfidz, al-muraqabah, and al-taqwim, which emphasize deliberation, trustworthiness, responsibility, justice, and continuous improvement.